THE INFLUENCE OF WORK ENVIRONMENT, EMPLOYEE RETENTION, AND PERCEIVED FAIRNESS ON PERCEIVED ORGANIZATIONAL SUPPORT (POS): A STUDY OF GRABBIKE PARTNERS IN SUKABUMI - Alya Salwa Fadhillah; Tetty Suffianty Zafar; R Deni Muhammad Danial (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This Study aims to determine the influence of Work Environment, Employee Retention and Perceived Fairness on Perceived Organizational Support (POS) on GrabBike partners in Sukabumi, Indonesia. As part of the growing gig economy, online motorcycle taxi drivers operate under a flexible and independent work structure, often without the benefits and protections of formal employment. Understanding what influences their perception of organizational support is critical to improving engagement, satisfaction, and long-term cooperation between drivers and platform providers. This study uses a quantitative approach with a survey method of 97 respondents who are active GrabBike partners in the Sukabumi area. Data was collected using a closed questionnaire and analyzed using multiple linear regression through the SPSS version 26 program. The results of the analysis show that Work Environment, Employee Retention and Perceived Fairness simultaneously have a significant effecton Perceived Organizational Support (POS). However, partially, Work Environment and Perceived Fairness have a positive and significant effect on Perceived Organizational Support (POS), while Employee Retention does not show a significant effect. The study highlights the importance of a supportive and comfortable work environment, as well as fair treatment in task allocation and compensation systems. These elements enhance the drivers' sense of belonging and trust toward the platform. Conversely, traditional retention strategies may not be as impactful in the gig economy, where work is often viewed as temporary or supplemental. The findings offer practical implications for digital platforms aiming to strengthen human resources and partner loyalty. Companies like Grab are encouraged to invest in transparent communication, flexible benefit schemes, and fair operational policies. This study contributes to the broader understanding of human resource manajement (HRM) in non-traditional employment sectors and aligns with the IICIS 2025 theme of “Food Security and Strengthening Human Resources.”